Cuento ilustrado sobre el Danzante de San Andrés de Píllaro, como medio de difusión cultural, dirigido a niños de la localidad - Quishpe Toapanta, Walter Cristobal (2024)
The objective of this project is to develop an illustrated story about the Dancer of San Andrés de Píllaro for children from 6 to 9 years old as a means of cultural dissemination, because the lack of editorial material about this character prevents knowledge about customs and traditions. Therefore, it is of great importance to propose solutions that, through graphic design, present the information collected to teach children about their culture and thus keep the cultural identity of the San Andrés parish alive. A deductive method with a qualitative approach was applied, carrying out bibliographic and field research. The collection of information was carried out through the application of interviews and observation sheets in order to obtain information about this emblematic character as well as identify the most appropriate style, graphic line and formats of children's stories. The proposal resulted in the design of an illustrated story with pop-up mechanisms, which captures children's attention and keeps them interested, facilitates a more effective understanding and retention of the cultural information presented, and stimulates their imagination and creativity. This interactive way of learning allows children to better visualize and understand cultural stories and traditions, creating a memorable and entertaining educational experience.